Laurence Sterne's A sentimental journey : a legacy to the world - Gerard, William Blake; Newbould, Mary-Céline (Bucknell University Press, 2021)
Laurence Sterne's A Sentimental Journey through France and Italy continues to be as widely read and admired as upon its first appearance. Deemed more accessible than Sterne's Life and Opinions of Tristram Shandy, Gentleman, and often assigned as a college text, A Sentimental Journey has received its share of critical attention, but--unlike Tristram Shandy--to date it has not been the subject of a dedicated anthology of critical essays. This volume fills that gap with fresh perspectives on Sterne's novel that will appeal to students and critics alike. Together with an introduction that situates each essay within A Sentimental Journey's reception history, and a tailpiece detailing the culmination of Sterne's career and his death, this volume presents a cohesive approach to this significant text that is simultaneously grounded and revelatory.